Composite coating material suitable for quartz product and preparation method of composite coating material
By setting up an adhesive layer, transition layer and protective layer on the surface of the quartz product, the problem of quartz pipes being susceptible to silicon erosion in the existing LPCVD process is solved, extending the service life of the quartz product and reducing costs.
Patent Information
- Application Number
- CN202411874932.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-19
AI Technical Summary
In the existing LPCVD process, quartz pipes are susceptible to silicon corrosion during silicon deposition, causing the pipe to explode and reduce their service life.
The adhesive layer, transition layer and protective layer are arranged in sequence on the surface of the quartz product, which play the role of adhesion, buffer isolation and strength protection respectively to prevent the deposition of the quartz product from damage to the deposited silicon.
It effectively prevents the deposition of deposited silicon to quartz products, extends the service life of quartz products, and reduces process costs.
Smart Images

Figure CN119899052A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating preparation, and in particular to a composite coating material suitable for quartz products and a preparation method thereof. Background Art
[0002] In the processing of photovoltaic and semiconductor products, LPCVD (Low Pressure Chemical Vapor Deposition) technology is often used. It is mainly used for material deposition processes, such as depositing oxide, nitride, polysilicon and other thin films on photovoltaic or semiconductor products.
[0003] The existing LPCVD process usually uses quartz tubes as reaction furnace tubes. During the silicon deposition process, since the deposition of the LPCVD process is not directional, a large amount of silicon will be deposited on the inner surface of the furnace tube. These deposited silicon will corrode the quartz tube, and the expansion coefficient of the silicon deposition layer is quite different from that of the quartz glass. Due to the effect of thermal stress, the furnace tube will also burst, reducing the service life of the tube. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and propose a composite coating material suitable for quartz products and a preparation method thereof. A bonding layer, a transition layer and a protective layer are sequentially arranged on the quartz product to respectively play the role of adhesion, buffer isolation and strength protection, which can effectively prevent the deposited silicon from damaging the quartz product, extend the service life of the quartz product and reduce the process cost.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] According to a first aspect of the present invention, a composite coating material suitable for a quartz product is provided, the composite coating material comprising a bonding layer disposed on a surface of the quartz product, a transition layer disposed on the bonding layer, and a protective layer disposed on the transition layer.
[0007] The coating of the bonding layer includes the following components in weight fractions: thickening binder: 5.0% to 25.0%, surfactant: 0.5% to 5.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature binder: 2.0% to 10.0%, and the balance is deionized water.
[0008] The coating of the transition layer includes the following components in weight fractions: thickening binder: 6.0% to 30.0%, surfactant: 0.5% to 6.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature binder: 2.0% to 10.0%, and the balance is deionized water.
[0009] The coating of the protective layer comprises the following components in weight fractions: thickening binder: 5.0% to 25.0%, surfactant: 0.5% to 5.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature binder: 2.0% to 10.0%, and the balance is deionized water.
[0010] Preferably, the ceramic functional additives in the coating of each layer include one or more of silicon nitride, silicon carbide, aluminum oxide, magnesium oxide, silicon oxide, zirconium oxide, boron nitride, and sodium silicate.
[0011] Furthermore, the ceramic functional additives in the coating of the bonding layer include silicon carbide, aluminum oxide, zirconium oxide, silicon oxide and magnesium oxide; the ceramic functional additives in the coating of the transition layer include silicon carbide, aluminum oxide, zirconium oxide, silicon oxide, magnesium oxide and silicon nitride; the ceramic functional additives in the coating of the protective layer include silicon carbide, aluminum oxide, zirconium oxide, silicon oxide, boron nitride and sodium silicate.
[0012] Furthermore, the ceramic functional additives in the coating of the bonding layer include: 2.0% to 15.0% silicon carbide, 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0.5% to 8.0% magnesium oxide, and 0.5% to 8.0% silicon nitride;
[0013] The ceramic functional additives in the coating of the transition layer include: 1.0% to 10.0% silicon carbide, 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0.5% to 8.0% magnesium oxide, and 0.5% to 10.0% silicon nitride;
[0014] The ceramic functional additives in the coating of the protective layer include: 2.0% to 15.0% silicon carbide, 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0% to 6.0% boron nitride, and 0.5% to 8.0% sodium silicate.
[0015] Preferably, the thickening binder is one or a combination of at least two of methyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, sodium carboxymethyl cellulose or a polyacrylic thickening binder.
[0016] Preferably, the high temperature binder is any one of silica sol and silicate or a combination of the two.
[0017] Preferably, the surfactant includes a dispersant, a leveling agent and a defoamer; the dispersant is one or more of acrylate ammonium salts or styrene maleic anhydride modified polymers; the defoamer is one or more of mineral oil defoamers or polyethylene glycols; the leveling agent is one or more of polyether modified silicone or acrylic leveling agents.
[0018] Preferably, the melting point of the low-melting-point glass powder is 200-850°C.
[0019] According to a second aspect of the present invention, a method for preparing the composite coating material suitable for quartz products as described above is provided, the method comprising: preparing an adhesive layer, a transition layer and a protective layer in sequence. The preparation steps of each layer include:
[0020] Step S1: weighing a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to proportion;
[0021] Step S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0022] Step S3: adding low melting point glass powder, high temperature binder and ceramic functional additive into the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0023] Step S4: adding deionized water to the second mixture to dilute it, then finely grinding the diluted mixture using a bead mill, and adjusting the viscosity to obtain a coating with the required viscosity and fineness;
[0024] Step S5: coating a coating with required viscosity and fineness onto the surface of the quartz product or the corresponding coating, and after drying, annealing the coated quartz product using an annealing furnace, and then cooling to room temperature.
[0025] Preferably, the dry film thicknesses of the bonding layer, the transition layer, and the protective layer are 0.01 to 0.5 mm, respectively. The viscosity of the coating obtained in the step S4 of preparing the bonding layer is greater than the viscosity of the coating obtained in the step S4 of preparing the transition layer, and the viscosity of the coating obtained in the step S4 of preparing the transition layer is greater than the viscosity of the coating obtained in the step S4 of preparing the protective layer.
[0026] Preferably, in step S5, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 180-220°C and kept warm for 20-40 minutes, the second stage is heated to 300-600°C and kept warm for 20-50 minutes, and the third stage is heated to 800-1100°C and kept warm for 30-180 minutes.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention sequentially arranges a bonding layer, a transition layer and a protective layer on the quartz product, which respectively play the role of adhesion, buffer isolation and strength protection, and the composite coatings cooperate with each other to effectively prevent the deposited silicon from damaging the quartz product, thereby extending the service life of the quartz product and reducing the process cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a structural diagram of the composite coating material of some embodiments of the present invention applied to quartz products.
[0029] Figure 2 The present invention is a flowchart of the steps for preparing each coating layer according to some embodiments of the present invention.
[0030] In the figure, 10 is a quartz product, 20 is a bonding layer, 30 is a transition layer, and 40 is a protective layer. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. It can be understood that some technical means of the various embodiments described herein can be replaced or combined with each other without conflict.
[0032] In the description of the present invention, if there are terms such as "first", "second", etc., they are only used to distinguish the objects described, and do not have any order or technical meaning. Therefore, the objects defined as "first", "second", etc. may explicitly or implicitly include one or more of the objects. In addition, "one" or "a" and similar words do not indicate a quantity limitation, but indicate the existence of at least one, and "multiple" means not less than two.
[0033] In the description of the present specification, reference to "one embodiment" or "some embodiments" etc. means that one or more embodiments of the present invention include a specific feature, structure or characteristic described in conjunction with the embodiment. Therefore, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. appearing in different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways.
[0034] According to a first aspect of the present invention, a composite coating material suitable for quartz products is provided. Figure 1In some embodiments, the composite coating material includes a bonding layer 20 disposed on the surface of the quartz product 10, a transition layer 30 disposed on the bonding layer 20, and a protective layer 40 disposed on the transition layer 30. The bonding layer 20 is prepared by applying the coating of the bonding layer and then annealing it, the transition layer 30 is prepared by applying the coating of the transition layer and then annealing it, and the protective layer 40 is prepared by applying the coating of the protective layer and then annealing it.
[0035] Among them, the coating of the bonding layer 20 includes the following components in weight fraction (as a percentage of the total weight of the coating of the bonding layer): thickening adhesive: 5.0% to 25.0%, surfactant: 0.5% to 5.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature adhesive: 2.0% to 10.0%, and the balance is deionized water.
[0036] The coating of the transition layer 30 includes the following components by weight fraction (as a percentage of the total weight of the coating of the transition layer): thickening binder: 6.0% to 30.0%, surfactant: 0.5% to 6.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature binder: 2.0% to 10.0%, and the balance is deionized water.
[0037] The coating of the protective layer 40 includes the following components by weight (in percentage of the total weight of the coating of the protective layer): thickening binder: 5.0% to 25.0%, surfactant: 0.5% to 5.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature binder: 2.0% to 10.0%, and the balance is deionized water. Further, the ceramic functional additive in the coating of the protective layer 40 is mainly sodium silicate.
[0038] In each coating, the combination of low melting point glass powder and ceramic functional additives can increase the bonding force between the coating and the quartz product and between each coating, improve the density and mechanical properties of the coating, and reduce the expansion coefficient of the coating. The above composite coating material is applied to the quartz product 10, and the bonding layer 20, the transition layer 30 and the protective layer 40 respectively play the role of adhesion, buffering isolation and strength protection. The composite coatings cooperate with each other to effectively prevent the deposited silicon from damaging the quartz product, extend the service life of the quartz product, and reduce the process cost.
[0039] In some preferred embodiments, in the coating of each layer, the ceramic functional additive can be one or more of silicon nitride (Si3N4), silicon carbide (SiC), aluminum oxide (Al2O3), magnesium oxide (MgO), silicon oxide (SiO2), zirconium oxide (ZrO2), boron nitride (BN), and sodium silicate (Na2O·nSiO2).
[0040] Among them, silicon nitride can improve the hardness, strength and wear resistance of the coating and increase durability. Silicon carbide can improve the hardness, wear resistance, chemical corrosion resistance, water resistance and weather resistance of the coating. Aluminum oxide can enhance the hardness, wear resistance, gloss and flatness of the coating. Magnesium oxide can significantly improve the hardness of the coating, improve the adhesion and durability of the coating, and also has good flame retardant properties, which can keep the coating stable in high temperature environments. Silicon oxide can be used as a filler to optimize the film-forming properties of the coating, so that the coating can quickly form a uniform and smooth coating. Zirconium oxide can increase the hardness, wear resistance, chemical resistance and leveling of the coating, while also improving gloss and stability. Boron nitride can enhance the mechanical strength, heat resistance, wear resistance, corrosion resistance of the coating, and can effectively resist thermal expansion in high temperature environments. Sodium silicate can be used to adjust the viscosity of the coating, improve the hiding power of the coating, and can also make the components in the coating evenly dispersed to prevent sedimentation or granular substances.
[0041] In other preferred embodiments, the ceramic functional additives in the coating of the bonding layer 20 include silicon carbide, aluminum oxide, zirconium oxide, silicon oxide and magnesium oxide; the ceramic functional additives in the coating of the transition layer 30 include silicon carbide, aluminum oxide, zirconium oxide, silicon oxide, magnesium oxide and silicon nitride; the ceramic functional additives in the coating of the protective layer 40 include silicon carbide, aluminum oxide, zirconium oxide, silicon oxide, boron nitride and sodium silicate.
[0042] In some preferred embodiments, the ceramic functional additives in the coating of the bonding layer 20 include: 2.0% to 15.0% silicon carbide (as a percentage of the total weight of the coating of the bonding layer), 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0.5% to 8.0% magnesium oxide, and 0.5% to 8.0% silicon nitride.
[0043] The ceramic functional additives in the coating of the transition layer 30 include: 1.0% to 10.0% silicon carbide (as a percentage of the total weight of the coating of the transition layer), 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0.5% to 8.0% magnesium oxide, and 0.5% to 10.0% silicon nitride.
[0044] The ceramic functional additives in the coating of the protective layer 40 include: 2.0% to 15.0% silicon carbide (as a percentage of the total weight of the coating of the protective layer), 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0 to 6.0% boron nitride, and 0.5% to 8.0% sodium silicate.
[0045] In some other embodiments, the coating of the bonding layer 20 includes the following components in weight fractions: thickening binder: 10.0% to 25.0%, high temperature binder: 2.0% to 8.0%, ceramic functional additive: 3.0% to 20.0%, low melting point glass powder: 3.0% to 10.0%, surfactant: 0.5% to 5.0%, and the balance is deionized water. Among them, the ceramic functional additive includes: silicon carbide 2.0% to 15.0% (accounting for the percentage of the total weight of the coating of the bonding layer), aluminum oxide 1.0% to 5.0%, zirconium oxide 0.1% to 6.0%, magnesium oxide 0.5% to 8.0%, and silicon nitride 0.5% to 8.0%.
[0046] The coating of the transition layer 30 includes the following components in weight fraction: thickening binder: 8.0% to 25.0%, high temperature binder: 2.0% to 10.0%, ceramic functional additive: 3.0% to 22.0%, low melting point glass powder: 3.0% to 10.0%, surfactant: 0.5% to 5.0%, and the balance is deionized water. Among them, the ceramic functional additive includes: silicon carbide 1.0% to 10.0% (accounting for the percentage of the total weight of the coating of the transition layer), aluminum oxide 1.0% to 5.0%, zirconium oxide 0.1% to 6.0%, magnesium oxide 0.5% to 8.0%, and silicon nitride 0.5% to 10.0%.
[0047] The coating of the protective layer 40 includes the following components in weight fraction: thickening binder: 10.0% to 25.0%, high temperature binder: 2.0% to 8.0%, ceramic functional additive: 3.0% to 20.0%, low melting point glass powder: 3.0% to 10.0%, surfactant: 0.5% to 5.0%, and the balance is deionized water. Among them, the ceramic functional additive includes: silicon carbide 2.0% to 15.0% (accounting for the percentage of the total weight of the coating of the protective layer), aluminum oxide 1.0% to 5.0%, zirconium oxide 0.1% to 6.0%, boron nitride 0.1% to 6.0%, sodium silicate 1.0% to 8.0%.
[0048] In some embodiments, the high temperature adhesive may be any one of silica sol or silicate or a combination of the two. The high temperature adhesive enables the coating material to maintain good bonding performance in a high temperature environment, and plays an anti-oxidation and heat insulation role.
[0049] In some embodiments, the thickening binder may be one or a combination of at least two of methyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, sodium carboxymethyl cellulose or polyacrylic thickening binders.
[0050] In some embodiments, the surfactant includes a dispersant, a leveling agent, and a defoamer. In the application, the dispersant can be one or more of acrylate ammonium salts or styrene maleic anhydride modified polymers; the defoamer can be one or more of mineral oil defoamers or polyethylene glycols; the leveling agent can be one or more of polyether modified silicone or acrylic leveling agents. Dispersants can make particles break more quickly, reduce the free energy of the solid-liquid interface, and make the coating material dispersed evenly and stably. Defoamers can suppress and eliminate foam to ensure the stability of the coating material. Leveling agents can improve the leveling and wettability of coating materials, reduce surface defects, and improve the quality of coatings.
[0051] In some embodiments, the low-melting glass powder can be a commercially available low-melting glass powder product, and the melting point of the low-melting glass powder is 200-850° C. The low-melting glass powder can improve the adhesion, toughness, wear resistance, heat resistance, and corrosion resistance of the coating material.
[0052] In some preferred embodiments, the viscosity of the coating of the bonding layer 20 is greater than the viscosity of the coating of the transition layer 30, and the viscosity of the coating of the transition layer 30 is greater than the viscosity of the coating of the protective layer 40. That is, the viscosities of the bonding layer coating, the transition layer coating, and the protective layer coating decrease in sequence. In this way, the bonding layer 10 can be closely combined with the quartz product 10, and can play a buffering and bonding role, thereby enhancing the adhesion and durability of the composite coating material.
[0053] The viscosity of each layer of coating can be tested by the four-cup coating method in the prior art, and the viscosity of the coating can be 15s to 55s ("s" means seconds, which refers to the time required for a specific volume of coating to flow out). For example, in one embodiment, the viscosity of the coating of the bonding layer is 25s to 55s, the viscosity of the coating of the transition layer is 20s to 50s, and the viscosity of the coating of the protective layer is 15s to 45s.
[0054] According to a second aspect of the present invention, a method for preparing the composite coating material as described above is provided, the method comprising: sequentially preparing a bonding layer 20, a transition layer 30 and a protective layer 40. That is, firstly preparing the bonding layer 20 on the quartz product 10, then preparing the transition layer 30 on the bonding layer 20, and then preparing the protective layer 40 on the transition layer 30.
[0055] Among them, refer to Figure 2 As shown, the preparation steps of each layer include:
[0056] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water in proportion.
[0057] S2: Evenly mix deionized water, thickening binder and surfactant to obtain a first mixture, wherein a dispersing machine in the prior art can be used to mix deionized water, thickening binder and surfactant for 10 to 30 minutes.
[0058] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 to 40 minutes using a disperser to obtain a second mixture. The disperser can be a disperser product in the prior art.
[0059] S4: Add deionized water to the second mixture to dilute it, then use a bead mill to finely grind the diluted mixture, and adjust the viscosity to obtain a coating with the required viscosity and fineness. The bead mill can use the bead mill products in the prior art, and the ball-to-material ratio during grinding is (1-3):1; the fineness of the coating after fine grinding (the particle size of the coating particles) is <15μm. The viscosity of the prepared coating can be tested using the four-cup coating method in the prior art, and the viscosity of the coating can be 15s to 55s ("s" means seconds, which refers to the time required to flow a specific volume of coating).
[0060] S5: Apply a coating with required viscosity and fineness to the surface of the quartz product or the corresponding coating, and after drying, use an annealing furnace to anneal the coated quartz product, and then cool it to room temperature to form the required coating.
[0061] Specifically, the steps of preparing the bonding layer 20 include:
[0062] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to the composition ratio of the coating of the bonding layer;
[0063] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0064] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0065] S4: adding deionized water to the second mixture to dilute it; then finely grinding the diluted mixture using a bead mill and adjusting the viscosity to obtain a coating required for the bonding layer;
[0066] S5: the coating is applied to the quartz product 10 , and after drying, the coated quartz product is annealed in an annealing furnace, and then cooled to room temperature, thereby forming a bonding layer 20 .
[0067] The preparation steps of the transition layer 30 include:
[0068] S1: Weigh thickening binder, surfactant, low melting point glass powder, high temperature binder, ceramic functional additive and deionized water according to the composition ratio of the coating of the transition layer;
[0069] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0070] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0071] S4: adding deionized water to the second mixture to dilute it; then finely grinding the diluted mixture using a bead mill and adjusting the viscosity to obtain the coating required for the transition layer;
[0072] S5: coating the coating on the bonding layer 20 , and then annealing the coated quartz product in an annealing furnace after drying, and then cooling to room temperature, so as to form a transition layer 30 .
[0073] The steps of preparing the protective layer 40 include:
[0074] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to the component proportion of the coating of the protective layer;
[0075] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0076] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0077] S4: adding deionized water to the second mixture to dilute it; then finely grinding the diluted mixture using a bead mill and adjusting the viscosity to obtain a coating required for the protective layer;
[0078] S5: coating the coating on the transition layer 30 , and performing annealing treatment on the coated quartz product, and then cooling to room temperature, so as to form a protective layer 40 .
[0079] The above-mentioned composite coating material is applied to quartz products, and the bonding layer, transition layer and protective layer play the role of adhesion, buffering isolation and strength protection respectively, that is, the bonding layer is used to make the composite coating material effectively adhere to the surface of the quartz product and improve the adhesion of the composite coating material, the middle transition layer can play the role of buffering isolation, and the outermost protective layer plays the role of strength protection; the composite coatings cooperate with each other to effectively prevent the deposited silicon from damaging the quartz product, extend the service life of the quartz product and reduce the process cost.
[0080] It should be noted that the thickness of each coating and the coating process can be reasonably set according to the actual situation. In some preferred embodiments, the dry film thickness of the bonding layer 20, the transition layer 30, and the protective layer 40 is 0.01-0.5 mm respectively. The bonding layer 20, the transition layer 30, and the protective layer 40 are respectively coated by pneumatic spray gun spraying to ensure the uniformity of the coating thickness.
[0081] Furthermore, the viscosity of the coating obtained in the step S4 of preparing the bonding layer is greater than the viscosity of the coating obtained in the step S4 of preparing the transition layer, and the viscosity of the coating obtained in the step S4 of preparing the transition layer is greater than the viscosity of the coating obtained in the step S4 of preparing the protective layer. That is, the viscosities of the bonding layer coating, the transition layer coating, and the protective layer coating decrease in sequence. In this way, the bonding layer can be closely combined with the quartz product, and can play a buffering and bonding role, thereby enhancing the adhesion and durability of the composite coating.
[0082] In one embodiment, the viscosity of the coating obtained in the bonding layer preparation step S4 is 25s-55s, the viscosity of the coating obtained in the transition layer preparation step S4 is 20s-50s, and the viscosity of the coating obtained in the protective layer preparation step S4 is 15s-45s.
[0083] In some embodiments, in step S5, the annealing temperature is 800-1100°C, and the annealing time is 0.5-3 hours. Further, the annealing temperature of the bonding layer is 1050°C, and the annealing time is 60 minutes; the annealing temperature of the transition layer is 1010°C, and the annealing time is 60 minutes; the annealing temperature of the protective layer is 950°C, and the annealing time is 45 minutes.
[0084] In other embodiments, in step S5 of each coating, the quartz product is annealed by a two-stage heating and insulation method: the first stage is heated to 300-600°C and kept warm for 20-50 minutes, and the second stage is heated to 800-1100°C and kept warm for 0.5-3 hours. The two-stage heating and insulation method is used to anneal the quartz product, which can fully volatilize the solvent and fully remove the binder at the medium and low temperature stage, obtain a good annealing effect, enhance the bonding strength and density between the coating material and the quartz product and between adjacent coatings, and improve the comprehensive performance of the coating material.
[0085] In some other embodiments, in each coating step S5, the coated quartz product is annealed by a three-stage heating and heat preservation method: the first stage is heated to 180-220°C and kept warm for 20-40 minutes, the second stage is heated to 300-600°C and kept warm for 20-50 minutes, and the third stage is heated to 800-1100°C and kept warm for 30-180 minutes. The three-stage heating and heat preservation method is used to anneal the quartz product, which can fully volatilize the solvent and fully remove the binder at the medium and low temperature stage, obtain a good annealing effect, enhance the bonding strength and density between the coating material and the quartz product and between adjacent coatings, and improve the comprehensive performance of the coating material.
[0086] Three embodiments and three comparative examples of the present invention are given below. In each embodiment or comparative example, 10 quartz tube products of the same batch and model are selected as test objects. In embodiments 1-3, the component ratio and preparation method of the composite coating material of the invention are used to coat 10 quartz tubes to form a three-layer composite coating; comparative example 1 adopts the component ratio of the bonding layer in embodiment 1 to coat 10 quartz tubes to form a single bonding layer coating, comparative example 2 adopts the component ratio of the protective layer in embodiment 1 to coat 10 quartz tubes to form a single protective layer coating, and in comparative example 3, 10 quartz tubes are not coated with any coating material. The average service life of the quartz tubes in each embodiment or comparative example is tested.
[0087] Table 1 shows the weight ratio of each component in the composite coating material in Example 1 and Example 2:
[0088] Table 1
[0089]
[0090] Table 2 shows the weight ratio of each component of the composite coating material in Example 3, and the weight ratio of the coating components in Comparative Examples 1-3:
[0091] Table 2
[0092]
[0093] Table 3 shows the average service life test results of the quartz tubes in Examples 1-3 and Comparative Examples 1-3:
[0094] Table 3
[0095] Coating conditions Average service life of quartz tube (days) Example 1 Three-layer composite coating 355 Example 2 Three-layer composite coating 347 Example 3 Three-layer composite coating 322 Comparative Example 1 Single adhesive layer 255 Comparative Example 2 Single layer of protection 241 Comparative Example 3 No coating 101
[0096] Embodiment 1:
[0097] The weight fraction of each component in the bonding layer coating is as follows: thickening binder: 17.0%, surfactant: 1.5%, ceramic functional additive: 9.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, water: 64.5%. Among them, the ceramic functional additive includes: silicon carbide: 2.0%, aluminum oxide: 4.0%, zirconium oxide: 0.5%, magnesium oxide: 1.5%, silicon nitride: 1.0%.
[0098] The steps for preparing the bonding layer are:
[0099] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to the composition ratio of the coating of the bonding layer;
[0100] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0101] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0102] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the bonding layer; use a coating cup to test the coating viscosity, which is 49s;
[0103] S5: The coating is applied to the quartz product, and the coated quartz product is annealed, and then cooled to room temperature to form a bonding layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0104] The weight fraction of each component in the transition layer is: thickening binder: 16.0%, surfactant: 1.5%, ceramic functional additive: 9.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, deionized water: 65.5%. Among them, the ceramic functional additive includes: silicon carbide: 3.0%, aluminum oxide: 3.0%, zirconium oxide: 0.5%, magnesium oxide: 1.5%, silicon nitride: 1.0%.
[0105] The preparation steps of the transition layer are:
[0106] S1: Weigh thickening binder, surfactant, low melting point glass powder, high temperature binder, ceramic functional additive and deionized water according to the composition ratio of the coating of the transition layer;
[0107] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0108] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0109] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the transition layer; use a coating cup to test the coating viscosity to find that it is 44s;
[0110] S5: The coating is applied to the bonding layer, and the coated quartz product is annealed, and then cooled to room temperature to form a transition layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0111] The weight fraction of each component in the protective layer is: thickening binder: 15.0%, surfactant: 1.5%, ceramic functional additive: 9.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, deionized water: 66.5%. Among them, the ceramic functional additive includes: silicon carbide: 4.0%, aluminum oxide: 2.0%, zirconium oxide: 0.5%, magnesium oxide: 1.5%, sodium silicate: 1.0%.
[0112] The steps for preparing the protective layer are:
[0113] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to the component proportion of the coating of the protective layer;
[0114] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0115] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0116] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the protective layer; use a coating cup to test the coating viscosity to find that it is 37s;
[0117] S5: The coating is applied to the transition layer, and the coated quartz product is annealed, and then cooled to room temperature to form a protective layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0118] After testing, the thermal expansion coefficient of the bonding layer prepared in Example 1 is 1.45×10 -6 K -1 The thermal expansion coefficient of the transition layer is 1.56×10 -6 K -1 The thermal expansion coefficient of the protective layer is 1.51×10 -6 K -1 The average service life of the quartz tube measured in Example 1 is 355 days.
[0119] Embodiment 2:
[0120] The weight fraction of each component in the bonding layer is: thickening binder: 17.0%, surfactant: 1.5%, ceramic functional additive: 9.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, deionized water: 64.5%. Among them, the ceramic functional additive includes: silicon carbide: 2.0%, aluminum oxide: 4.0%, zirconium oxide: 1.0%, magnesium oxide: 1.0%, silicon nitride: 1.0%.
[0121] The steps for preparing the bonding layer are:
[0122] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to the composition ratio of the coating of the bonding layer;
[0123] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0124] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0125] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the bonding layer; use a coating cup to test the coating viscosity, which is 46s;
[0126] S5: The coating is applied to the quartz product, and the coated quartz product is annealed, and then cooled to room temperature to form a bonding layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0127] The weight fraction of each component in the transition layer coating is as follows: thickening binder: 16.0%, surfactant: 1.5%, ceramic functional additive: 9.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, deionized water: 65.5%. Among them, the ceramic functional additive includes: silicon carbide: 3.0%, aluminum oxide: 3.0%, zirconium oxide: 1.0%, magnesium oxide: 1.0%, silicon nitride: 1.0%.
[0128] The preparation steps of the transition layer are:
[0129] S1: Weigh thickening binder, surfactant, low melting point glass powder, high temperature binder, ceramic functional additive and deionized water according to the composition ratio of the coating of the transition layer;
[0130] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0131] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0132] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the transition layer; use a coating cup to test the coating viscosity to find that it is 42s;
[0133] S5: The coating is applied to the bonding layer, and the coated quartz product is annealed, and then cooled to room temperature to form a transition layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0134] The weight fraction of each component in the protective layer is: thickening binder: 15.0%, surfactant: 1.5%, ceramic functional additive: 9.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, deionized water: 66.5%. Among them, the ceramic functional additive includes: silicon carbide: 4.0%, aluminum oxide: 2.0%, zirconium oxide: 1.0%, magnesium oxide: 1.0%, sodium silicate: 1.0%.
[0135] The steps for preparing the protective layer are:
[0136] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to the component proportion of the coating of the protective layer;
[0137] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0138] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0139] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the protective layer; use a coating cup to test the coating viscosity to be 35s;
[0140] S5: The coating is applied to the transition layer, and the coated quartz product is annealed, and then cooled to room temperature to form a protective layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0141] After testing, the thermal expansion coefficient of the bonding layer prepared in Example 2 is 1.42×10 -6 K -1 The thermal expansion coefficient of the transition layer is 1.53×10 -6 K -1 The thermal expansion coefficient of the protective layer is 1.49×10 -6 K -1 The average service life of the quartz tube measured in Example 2 is 347 days.
[0142] Embodiment 3:
[0143] The weight fraction of each component in the bonding layer coating is as follows: thickening binder: 17.0%, surfactant: 1.5%, ceramic functional additive: 10.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, deionized water: 63.5%. Among them, the ceramic functional additive includes: silicon carbide: 3.0%, aluminum oxide: 4.0%, zirconium oxide: 0.5%, magnesium oxide: 1.5%, silicon nitride: 1.0%.
[0144] The steps for preparing the bonding layer are:
[0145] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to the composition ratio of the coating of the bonding layer;
[0146] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0147] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0148] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the bonding layer; use a coating cup to test the coating viscosity, which is 52s;
[0149] S5: The coating is applied to the quartz product, and the coated quartz product is annealed, and then cooled to room temperature to form a bonding layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0150] The weight fraction of each component in the transition layer coating is: thickening binder: 16.0%, surfactant: 1.5%, ceramic functional additive: 10.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, deionized water: 64.5%. Among them, the ceramic functional additive includes: silicon carbide: 4.0%, aluminum oxide: 3.0%, zirconium oxide: 0.5%, magnesium oxide: 1.5%, silicon nitride: 1.0%.
[0151] The preparation steps of the transition layer are:
[0152] S1: Weigh thickening binder, surfactant, low melting point glass powder, high temperature binder, ceramic functional additive and deionized water according to the composition ratio of the coating of the transition layer;
[0153] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0154] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0155] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the transition layer; use a coating cup to test the coating viscosity, which is 47s;
[0156] S5: The coating is applied to the bonding layer, and the coated quartz product is annealed, and then cooled to room temperature to form a transition layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0157] The weight fraction of each component in the protective layer is: thickening binder: 15.0%, surfactant: 1.5%, ceramic functional additive: 10.0%, low melting point glass powder: 4.0%, high temperature binder: 4.0%, deionized water: 65.5%. Among them, the ceramic functional additive includes: silicon carbide: 5.0%, aluminum oxide: 2.0%, zirconium oxide: 0.5%, magnesium oxide: 1.5%, sodium silicate: 1.0%.
[0158] The steps for preparing the protective layer are:
[0159] S1: Weigh a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to the component proportion of the coating of the protective layer;
[0160] S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture;
[0161] S3: adding low melting point glass powder, high temperature binder and ceramic functional additive to the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture;
[0162] S4: Add deionized water to the second mixture to dilute it; then use a bead mill to finely grind the diluted mixture and adjust the viscosity to obtain the coating required for the protective layer; use a coating cup to test the coating viscosity to find that it is 42s;
[0163] S5: The coating is applied to the transition layer, and the coated quartz product is annealed, and then cooled to room temperature to form a protective layer. During the annealing process, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1050°C and kept warm for 100 minutes.
[0164] After testing, the thermal expansion coefficient of the adhesive layer prepared in Example 3 is 1.49×10 -6 K -1 The thermal expansion coefficient of the transition layer is 1.63×10 -6 K -1 The thermal expansion coefficient of the protective layer is 1.57×10 -6 K -1 The average service life of the quartz tube measured in Example 3 is 322 days.
[0165] Comparative Example 1:
[0166] The single bonding layer coating was coated on the surface of the quartz tube using the component ratio of the bonding layer coating in Example 1. According to the test, the average service life of the quartz tube in Comparative Example 1 was 255 days.
[0167] Comparative Example 2:
[0168] The protective layer coating was coated on the surface of the quartz tube using the component ratio of the protective layer coating in Example 1. According to the test, the average service life of the quartz tube in Comparative Example 2 was 241 days.
[0169] Comparative Example 3:
[0170] The surfaces of the 10 quartz tube products were not coated with any coating material. After testing, the average service life of the quartz tubes in Comparative Example 3 was 101 days.
[0171] Comparing the test results of the above embodiments and comparative examples, it can be seen that:
[0172] Compared with the case of no coating in Comparative Example 3, the coating is formed on the quartz tube products in Examples 1-3 and Comparative Examples 1-2, and the average service life of the coated quartz tubes is extended. In addition, compared with the case of a single coating in Comparative Examples 1-2, the average service life of the quartz tubes with composite coatings in Examples 1-3 is significantly longer.
[0173] Comparative Examples 1 and 2 both use a single coating structure. From the use results, it can be seen that the single coating has a certain degree of extension effect on the service life of the quartz tube: compared with the uncoated case of Comparative Example 3, the average service life of the quartz tube in Comparative Example 1 is extended by 154 days, and the average service life of the quartz tube in Comparative Example 2 is extended by 140 days.
[0174] Compared with the case of no coating in comparative example 3, the composite coating materials prepared on the surface of the quartz tube in examples 1-3 have an average service life of the quartz tube extended to more than three times the original. Specifically, the average service life of the quartz tube in example 1 is extended by 254 days, the average service life of the quartz tube in example 2 is extended by 246 days, and the average service life of the quartz tube in example 3 is extended by 221 days. It can be seen that after adopting the composite coating material and preparation method of the present invention, the composite coatings cooperate with each other, which can effectively prevent the deposited silicon from damaging the quartz product, greatly extend the service life of the quartz product, and reduce the process cost.
[0175] Compared with Example 1, Example 2 adjusted the ratio of magnesium oxide (adjusted from 1.5% to 1.0%) and zirconium oxide (adjusted from 0.5% to 1.0%), the viscosity of the coating did not change much, the thermal expansion coefficient was slightly reduced, and the average service life of the quartz tube in Example 1 was slightly longer than the average service life of the quartz tube in Example 2. Compared with Example 1, Example 3 adjusted the ratio of silicon carbide (adjusted from 2%, 3%, and 4% to 3%, 4%, and 5%), the viscosity of the coating and the thermal expansion coefficient were increased, and the average service life of the quartz tube in Example 1 was longer than the average service life of the quartz tube in Example 3.
[0176] In general, the application effect of Example 1 is the best. Compared with the case of no coating in Comparative Example 3, the average service life of the quartz tube in Example 1 is extended by 254 days. Therefore, in practical applications, the component ratio and preparation method in Example 1 can be preferably adopted.
[0177] In summary, the present invention provides a composite coating material suitable for quartz products and a preparation method thereof. An adhesive layer, a transition layer and a protective layer are sequentially arranged on the quartz product to respectively play the role of adhesion, buffering isolation and strength protection. The composite coatings cooperate with each other to effectively prevent the deposited silicon from damaging the quartz product, thereby extending the service life of the quartz product and reducing the process cost.
[0178] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.
Claims
1. A composite coating material suitable for quartz products, characterized in that: The composite coating material comprises a bonding layer disposed on the surface of the quartz product, a transition layer disposed on the bonding layer, and a protective layer disposed on the transition layer; The coating of the bonding layer includes the following components by weight: thickening binder: 5.0% to 25.0%, surfactant: 0.5% to 5.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature binder: 2.0% to 10.0%, and the balance is deionized water; The coating of the transition layer includes the following components by weight: thickening binder: 6.0% to 30.0%, surfactant: 0.5% to 6.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature binder: 2.0% to 10.0%, and the balance is deionized water; The coating of the protective layer includes the following components in weight fractions: thickening binder: 5.0% to 25.0%, surfactant: 0.5% to 5.0%, ceramic functional additive: 3.0% to 25.0%, low melting point glass powder: 2.0% to 10.0%, high temperature binder: 2.0% to 10.0%, and the balance is deionized water.
2. The composite coating material suitable for quartz products according to claim 1, characterized in that: The ceramic functional additives in the coating of the bonding layer include: 2.0% to 15.0% silicon carbide, 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0.5% to 8.0% magnesium oxide, and 0.5% to 8.0% silicon nitride; The ceramic functional additives in the coating of the transition layer include: 1.0% to 10.0% silicon carbide, 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0.5% to 8.0% magnesium oxide, and 0.5% to 10.0% silicon nitride; The ceramic functional additives in the coating of the protective layer include: 2.0% to 15.0% silicon carbide, 1.0% to 10.0% aluminum oxide, 0.1% to 6.0% zirconium oxide, 0% to 6.0% boron nitride, and 0.5% to 8.0% sodium silicate.
3. The composite coating material suitable for quartz products according to claim 1, characterized in that: The high temperature adhesive is any one of silica sol and silicate or a combination of the two.
4. The composite coating material suitable for quartz products according to claim 1, characterized in that: The thickening binder is one or a combination of at least two of methyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, sodium carboxymethyl cellulose or polyacrylic acid thickening binders.
5. The composite coating material suitable for quartz products according to claim 1, characterized in that: The surfactant includes a dispersant, a leveling agent and a defoamer; the dispersant is one or more of acrylic acid ammonium salts or styrene maleic anhydride modified polymers; the defoamer is one or more of mineral oil defoamers or polyethylene glycols; the leveling agent is one or more of polyether modified silicone or acrylic leveling agents.
6. The composite coating material suitable for quartz products according to claim 1, characterized in that: The melting point of the low-melting-point glass powder is 200-850°C.
7. A method for preparing a composite coating material suitable for quartz products according to any one of claims 1 to 6, characterized in that: The bonding layer, transition layer and protective layer are prepared in sequence; wherein the preparation steps of each layer include: Step S1: weighing a thickening binder, a surfactant, a low melting point glass powder, a high temperature binder, a ceramic functional additive and deionized water according to proportion; Step S2: uniformly mixing deionized water, thickening binder, and surfactant to obtain a first mixture; Step S3: adding low melting point glass powder, high temperature binder and ceramic functional additive into the first mixture, and dispersing for 20 minutes to 40 minutes using a disperser to obtain a second mixture; Step S4: adding deionized water to the second mixture to dilute it, then finely grinding the diluted mixture using a bead mill, and adjusting the viscosity to obtain a coating with the required viscosity and fineness; Step S5: coating a coating with required viscosity and fineness onto the surface of the quartz product or the corresponding coating, and after drying, annealing the coated quartz product using an annealing furnace, and then cooling to room temperature.
8. The method for preparing a composite coating material suitable for quartz products according to claim 7, characterized in that: The dry film thicknesses of the bonding layer, the transition layer, and the protective layer are 0.01 to 0.5 mm, respectively; the viscosity of the coating obtained in the bonding layer preparation step S4 is greater than the viscosity of the coating obtained in the transition layer preparation step S4, and the viscosity of the coating obtained in the transition layer preparation step S4 is greater than the viscosity of the coating obtained in the protective layer preparation step S4.
9. The method for preparing a composite coating material suitable for quartz products according to claim 7, characterized in that: In step S5, the coated quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 180-220°C and kept warm for 20-40 minutes, the second stage is heated to 300-600°C and kept warm for 20-50 minutes, and the third stage is heated to 800-1100°C and kept warm for 30-180 minutes.
Citation Information
Patent Citations
Inner surface coating of quartz crucible and preparation method of coating
CN109627050A
Preparation method of dense quartz crucible high-purity coating
CN111589678A
High-temperature-resistant and anti-oxidation ceramic coating as well as preparation method and application thereof
CN115636692A
Coating, quartz tube containing same and application
CN116970294A
Crucible coating as well as preparation method and application thereof
CN118373710A
Cited By
Multi-element oxide ceramic coating refractory brick material containing reinforcement phase and preparation method thereof
CN121470993A